KORELASI ASPEK BUDAYA DENGAN MINAT IBU MENGGUNAKAN IUD SEBAGAI ALAT KONTRASEPSI - Badariati Badariati; Nur Sri Atik; Fransiska Firna; Eny Sendra (Ensiklopedia of Journal, 2026)
Based on the results of data collection, the use of long-term contraceptive methods, particularly intrauterine devices (IUDs), is still relatively low at the Sungai Bulian Community Health Center compared to other contraceptive methods. The purpose of this study was to correlate cultural aspects with mothers' interest in using IUDs as a contraceptive method. The research design used in this study was cross-sectional. The study was conducted in the working area of the Sungai Bulian Community Health Center in November 2024. The population consisted of all active family planning acceptors, with a sample size of 70 people. The sampling technique used probability sampling with purposive sampling. The research instrument used a research questionnaire. Data analysis was performed using univariate and bivariate analysis. The results showed a significant relationship between cultural aspects (p value: 0.004) and mothers' interest in using intrauterine devices (IUDs) as contraception. It is recommended that the Community Health Center improve public understanding by engaging with the community. It is necessary to change the knowledge and socio-cultural beliefs of the community regarding misconceptions about IUDs, especially among women of childbearing age, by providing counseling and education.Keywords: Culture, Intrauterine Device (IUD), Contraception